If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2x + 1) = 5 Reorder the terms: (1 + -2x) = 5 Remove parenthesis around (1 + -2x) 1 + -2x = 5 Solving 1 + -2x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 5 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 5 + -1 -2x = 5 + -1 Combine like terms: 5 + -1 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| x+15=4x+20 | | -.5(8+x)=-16 | | 49x=-8 | | -2x^4+5x^2-x-1=0 | | 8z^2-45z=-5z^3+72 | | x+(-20)=20 | | 1-(-3)=9 | | 2x+3y=4(x+y) | | W^2+6W-10=0 | | 6x+177+4x+93=180 | | 2x-3x-12=x+6x-4 | | 27=7x+2x | | 8x+6y-3=o | | 70+4y= | | 4s^3-16s=2s^2-8 | | A(a+5)-a= | | 5(g-2)+g=6(g-2) | | 4P+9=-8P | | 2e^2x-6=0 | | 35=12w-5w | | 4x^2+4y^2+4x-8y-59=0 | | 2-y=17 | | 12y=3y^3+9y^2 | | 2x-5=7+4y | | 8x-14+5x-27=180 | | sinx+7cosx=2 | | 8x^2-336=8x | | 2m^3+m^2-m=0 | | (6-3x)(8+3x)=48 | | 120=(x+20)+3x | | 17x-6=14x-15 | | 4x^2+12=24 |